Capital Flows to Brazil : The Endogeneity of Capital Controls - Cardoso, Eliane; Goldfajn, Ilan. (Washington, D.C. : International Monetary Fund, 1997)
This paper creates an index of capital controls to analyze the determinants of capital flows to Brazil, accounting for the endogeneity of capital controls by considering a government that sets controls in response to capital flows. It finds that the government reacts strongly to capital flows by increasing controls on inflows during booms and relaxing them in moments of distress. The paper estimates a vector autoregression with capital flows, controls, and interest differentials. It shows that controls have been temporarily effective in altering levels and composition of capital flows but have had no sustained effects in the long run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet